2010
DOI: 10.3357/asem.2578.2010
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Efficiency in Trained and Sedentary Rats After Exposure to Normobaric and Hyperbaric Oxygen

Abstract: Our results suggest that exposure to 100% normobaric oxygen for 24 h and HBO at 2 ATA for 4 h induces a reduction in the energetic efficiency of trained rats, but improves energetic efficiency in sedentary rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…To our knowledge, a standardized or commonly accepted method of progressive overload, which takes into account these key considerations, is currently unavailable. Previous investigations that have described a progressive overload have typically done so by increasing a combination of treadmill speed, incline, and exercise duration (Powers et al 1990;Criswell et al 1993;Mokelke et al 1997;Eddington et al 1998;Fiebig et al 1998;Demirel et al 1999;Noble et al 1999;Braga et al 2000;González et al 2000;Machida et al 2000;Jew and Moore 2002;Troxell et al 2003;Jafari et al 2005;Peres et al 2005;Ghanbari-Niaki 2006;Mueller and Hasser 2006;Yang et al 2006;Ghanbari-Niaki et al 2007;Leandro et al 2007;Mueller 2007;Harris et al 2008;Vichaiwong et al 2009;Eynan et al 2010). However, the descriptions of the increases in intensity or duration have often not been implemented in a systematic or standardized way, and as such a dose-response relationship cannot be discerned.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, a standardized or commonly accepted method of progressive overload, which takes into account these key considerations, is currently unavailable. Previous investigations that have described a progressive overload have typically done so by increasing a combination of treadmill speed, incline, and exercise duration (Powers et al 1990;Criswell et al 1993;Mokelke et al 1997;Eddington et al 1998;Fiebig et al 1998;Demirel et al 1999;Noble et al 1999;Braga et al 2000;González et al 2000;Machida et al 2000;Jew and Moore 2002;Troxell et al 2003;Jafari et al 2005;Peres et al 2005;Ghanbari-Niaki 2006;Mueller and Hasser 2006;Yang et al 2006;Ghanbari-Niaki et al 2007;Leandro et al 2007;Mueller 2007;Harris et al 2008;Vichaiwong et al 2009;Eynan et al 2010). However, the descriptions of the increases in intensity or duration have often not been implemented in a systematic or standardized way, and as such a dose-response relationship cannot be discerned.…”
Section: Discussionmentioning
confidence: 90%
“…From the available studies that have reported initial and terminal training intensity and duration, we estimated that a progression in treadmill speed of ∼1 m·min -1 ·day -1 may be achievable (Mokelke et al 1997;Eddington et al 1998;Fiebig et al 1998;Demirel et al 1999;Noble et al 1999;Braga et al 2000;González et al 2000;Machida et al 2000;Jew and Moore 2002;Jafari et al 2005;Peres et al 2005;Yang et al 2006;GhanbariNiaki et al 2007;Leandro et al 2007;Mueller 2007;Harris et al 2008;Vichaiwong et al 2009;Eynan et al 2010). The mean daily increase in treadmill speed was between 0.6 and 0.8 m·min -1 ·day -1 in the mild-, moderate-, and heavy-intensity trained rodents.…”
Section: Non-interval-based Trainingmentioning
confidence: 95%
“…Preexposure to HBO did not affect the submaximal heart rate (HR) or HR max (47,59,75) nor did it affect V E , blood lactate concentration, lactate threshold, ventilation threshold, or ventilatory equivalent for oxygen (10,27,59,75). In human studies, the RER was not affected by preexposure to HBO (10,75); however, the RER was decreased in trained but increased in sedentary rats (19). Using near-infrared spectroscopy (NIRS), Kawada et al (33) showed an improvement in muscle oxygenation, which is in contrast to the study of Webster et al (75) who failed to show any improvement in muscle oxygenation as assessed by NIRS.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Hodges et al (27) showed a decrease in the transcutaneous pO 2 in the lower limb already 10 minutes after finishing the HBO treatment, reaching values even lower than before HBO and speculated that this drop might either reflect the effect of tissue autoregulation or the vasoconstrictive effect of high pO 2 . Interestingly, although the exposure to HBO in different studies lasted between 50 minutes (33) to up to 6 hours (19), no significant ergogenic effects were found (19,27,33,44,47,59,75), addressing the need to more thoroughly investigate effects of HBO on tissue oxygenation. There is only 1 available study, performed by Čabrić et al (10), that did prove ergogenic effects of HBO treatment, namely, a higher V̇ o 2 max and higher velocity on a treadmill, persisting as long as 3 hours after 60-minute exposure to HBO at 2.8 ATA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the beneficial effects of hyperoxic gas administration during exercise are well documented (Wilson & Welch 1975, Tucker et al. 2007), the potential ergogenic action of pre‐exposure to O 2 to subsequent physical performance is doubtful (Eynan et al. 2010, Sperlich et al.…”
mentioning
confidence: 99%